If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(t + -1) + 8t = 7t + -3 Reorder the terms: -5(-1 + t) + 8t = 7t + -3 (-1 * -5 + t * -5) + 8t = 7t + -3 (5 + -5t) + 8t = 7t + -3 Combine like terms: -5t + 8t = 3t 5 + 3t = 7t + -3 Reorder the terms: 5 + 3t = -3 + 7t Solving 5 + 3t = -3 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 5 + 3t + -7t = -3 + 7t + -7t Combine like terms: 3t + -7t = -4t 5 + -4t = -3 + 7t + -7t Combine like terms: 7t + -7t = 0 5 + -4t = -3 + 0 5 + -4t = -3 Add '-5' to each side of the equation. 5 + -5 + -4t = -3 + -5 Combine like terms: 5 + -5 = 0 0 + -4t = -3 + -5 -4t = -3 + -5 Combine like terms: -3 + -5 = -8 -4t = -8 Divide each side by '-4'. t = 2 Simplifying t = 2
| -7+n=3 | | .18(y-5)+.12y=.20y-.01(60) | | 156-6x=4x+6 | | 30=8x | | 2a+68=(a+27)(7) | | 2a+68=(a+27)7 | | -5x-9x=-98 | | p(x)=x^6+19x^3-216 | | x^6+19x^3-216= | | 8x-7=36x+14 | | -3+12=13x-4-12x | | x*x*x+6x*x+17=0.7 | | 35(x-3)= | | 35x-105= | | x=0.7 | | x^3+y^3=0 | | a^3+b^3=0 | | 7n-n=24 | | 8p=6q+48 | | 4cosx+6cos^3x+6sin^3x=0 | | 7x^2+14x+24=0 | | x-8x^2=7 | | 14-22y=18x | | 0=-2y+10-6x | | 20=-10x-10y | | 2(x+7)11= | | -4y-11x=36 | | 10(x+2)=5(x+8) | | .5x^2-.5= | | -11x=-20+9y | | -11x=-20+9yu | | 3(t-3)=13 |